Экспериментальное обоснование диагностической значимости коэффициента нитротирозин/глутатион в клинической биохимии для оценки степени тяжести мозгового инсульта - Горбачева, С. В.; Беленичев, И. Ф.; Горбачова, Світлана Василівна; Бєленічев, Ігор Федорович; Gorbacheva, S. V.; Belenichev, I. F. (My University, 2016)
Спряженість в системі «NO – відновлені тіоли» відіграє істотну роль у механізмах нейродеструкції та ендогенної нейропротекції, а її співвідношення визначає долю нейрона в умовах церебральної ішемії. Ключовим фактором рівноваги в цій системі є підтримка на певному рівні пулу відновлених тіолів і, особливо глутатіону. Відновлені еквіваленти глутатіону забезпечують не тільки біодоступність NO, а й безпеку функціонування системи NO для нейрона, попереджаючи утворення його нейротоксичних дериватів. Виявлена статистично достовірна лінійна залежність ступеня тяжкості неврологічного дефіциту від функціонування системи «NO – відновлені тіоли». Отримані результати є експериментальним обґрунтуванням застосування в клінічній біохімії коефіцієнта нітротирозин/відновлений глутатіон в якості діагностичного критерію ступеня тяжкості мозкового інсульту. Essential disadvantages take place in laboratory diagnostics of estimation the severity of acute cerebral circulation impairments. Modern laboratory parameters and instrumental methods used nowadays reveal deeper and not very reversible cerebral tissue damages. Experimental investigations reflect a role of impairments of glutathione and NO system in pathogenesis of ischemic neurodestruction. Detection of glutathione and NO system regularities response in brain to acute cerebral ischemia is an important problem of modern clinical biochemistry. The decision of the given problem could promote a significant growth in rendering assistance to the patients due to purposeful improvement of the methods of pharmacological correction. The purpose of the given investigation is to reveal correlation dependence on the base of experimental data between neurological impairments among the animals with acute cerebral circulation impairment of different degree of severity and nitrotyrosine/glutathione ratio in brain. The conducted investigations showed that in cerebral tissues of animals with slight neurologic deficiency (average grade – 2,4) it was observed the drop of reduced glutathione form contents on 47,6% and accumulation of nitrotyrosine on 93,8%. That is the evidence of oxidative and nitrosative stresses development. Further worsening of neurologic impairments was accompanied by pathobiochemical reactions progress. Among the animals with severe neurologic impairments in cerebral tissues it was observed essential increase of nitrotyrosine level that is a marker of the most toxic product of nirtosative stress such as peroxynitrite. Intensified formation of peroxynitrite is specified by thiol-disulfide balance shift inside neurons. The decrease of reduced glutathione concentration was occurring simultaneously with the process of nitrotyrosine accumulation and neurologic deficiency formation. Conjugation in the system “nitric oxide – reduced thiols” plays a significant role in mechanisms of neurodestruction and endogenous neuroprotection and its correlation defines neuron destiny in conditions of cerebral ischemia. Key factor of balance in this system is a maintenance at definite level the pool of reduced thiols in particular glutathione. Reduced equivalents of glutathione provide not only bioavailability of nitric oxide but also safety of NO system functioning for a neuron preventing a formation of its neurotoxic derivatives. A statistically significant linear dependence of neurologic deficiency manifestation degree from functioning of conjugated system “nitric oxide – reduced thiols” was established. The obtained results are considered to be an experimental justification of nitrotyrosine/ reduced glutathione coefficient application in clinical biochemistry as a diagnostic criterion of cerebral stroke severity.
Експериментальне обґрунтування діагностичної значущості коефіцієнта нітротирозин/глутатіон в клінічній біохімії для оцінки ступеня тяжкості мозкового інсульту
Experimental justification of diagnostic significance of nitrotyrosine/glutathione coefficient in clinical biochemistry in order to give an estimation of cerebral stroke severity
Keywords: нітротирозин; глутатіон; оксид азоту; гостре порушення мозкового кровообігу; nitrotyrosine; glutathione; nitric oxide; acute cerebral circulation impairment